A Literature Review of Adult Students' Reading Comprehension: Inputs for Distance Education in Costa Rica - Poltronieri Méndez, Sarita (2022)
Reading comprehension is of the utmost importance in distance education since the written text still remains the prevailing way to transmit information in classes. The purpose of this paper is to describe the way in which reading comprehension of adult learners, especially university students, is documented through a literature review to generate helpful inputs for decision making in distance education in Costa Rica. A systematic literature review was carried out in three stages, which included a review protocol, Boolean operators use (AND + / OR = / NOT -), inclusion and exclusion document criteria, as well as four databases to search documents. The main finding shows that there is no official measurement unit or agreement on a parameter for reporting reading comprehension. Its measurement is done using percentages, words per minute (X̅=183,05 ± 68,92) and other indicators (statistics). Therefore, it was concluded that the actual reading comprehension capacity in distance education students is yet unknown in Costa Rica, and that it is necessary to make use of more than one input to determine reading comprehension. Also, it is necessary to explore the use of information and communication technologies (ICT) for a more assertive collection of adult reading comprehension data.